The Effects of Climate Change on Geological Structures in coastline Regions - Mohamed Khalifa Hassen Musa (African Journal of Advanced Pure and Applied Sciences, 2025)
Climate change is reshaping coastal zones by altering geomorphology and undermining geological stability. This article synthesizes evidence on three interlinked pathways—coastal erosion, seawater intrusion, and geohazard amplification—and explains how sea-level rise, intensifying storms, and anthropogenic pressure accelerate shoreline retreat, topsoil loss, and habitat degradation. We show that salinization of coastal aquifers reduces freshwater availability, degrades soil structure, and compromises agricultural output and critical infrastructure, thereby heightening risks of landslides, liquefaction, and structural failure. Cross-regional cases from the Niger Delta, Pakistan, and the Mediterranean demonstrate both the breadth of these impacts and the local specificities that shape exposure and vulnerability. The paper also evaluates intervention options spanning hard-engineering works, groundwater control, and GIS-supported risk mapping, alongside nature-based measures such as mangrove and wetland restoration. Finally, we outline adaptation and policy priorities to safeguard ecosystems and settlements, arguing for integrated coastal management that couples spatial planning with scenario-led monitoring to build resilience under ongoing climatic change.